Concrete damage–plasticity model with double independent hardening - A. M. Budarin; G. I. Rempel; A. A. Kamzolkin; V. N. Alekhin (Vestnik MGSU)
Introduction. Being an integral part of the modern construction, concrete is a complex nonlinear material. The behaviour of concrete depends to a large extent on stress–strain state and loading history. Among the structures of newly constructed and reconstructed buildings, there are a large number of elements operating in the conditions of the triaxial stress–strain state, alternating and cyclic loading. A phenomenological material model used in the numerical methods can serve as a universal tool that allows to describe the behavior of concrete under such conditions. The aim of the research is to develop the concrete model that allows to simulate material behavior with sufficient accuracy under static short-term loading. The model should reflect the key features, which characterizes the behaviour of concrete and have an algorithm for regularizing the problem of localization of irreversible deformations.Materials and methods. This research is based on the analytical generalization and systematization of the data received from domestic and foreign sources devoted to the plasticity theory and fracture mechanics of concrete and reinforced concrete.Results. The model was implemented in the ANSYS finite-element software package, with the help of which it is possible to apply custom material models. Comparison of the laboratory and numerical results for concrete and reinforced concrete was made.Conclusions. The presented model allows to simulate behavior of concrete with substantial accuracy within the static short-term loading and reflects main features of the material behavior. To regularize the problem of localization of irreversible deformations, the model uses an approach based on the crack band theory. The values of all parameters required for the utilisation of the material model are presented.